Perspectiva sócio-histórica da educação terapêutica do paciente: O corpo explicado - Dos Santos Mamed, Marcelo (My University, 2020)
Due to the high prevalence of diabetes in the world, educational approach has been gradually introduced as a strategy to hinder its potential complications. Therapeutic patient education (TPE) is rarely described as a practice, although it is recognised as an effective strategy and as a new form of relationship in health care. Studies related to TPE have largely focused on the biomedical results of these interventions. By means of explanation, the main discursive procedure for the professional activity of TPE, doctors, nurses and dietitians align themselves in the transmission of the knowledge that is necessary for the daily management of diabetes. Inspired by a socio-historical perspective, this article offers an analysis of the explanation as a situated professional activity. Using theoretical tools from disciplines such as Linguistics and Clinic of Activity, this study attempts to understand the accomplishment of the explanation in this specific context of health care. Using a simple self-confrontation method, we propose an analysis of Denise’s (a dietitian who works in a TPE team in the French-speaking region of Switzerland) explanation in two ways: a) the interactive analysis of the explanation; b) Denise’s discourse analysis as she analyses her own explanatory activity while watching a recorded video. The analysis points to the explanatory process as an interactive and dialogical accomplishment which updates the representations of the body and the patient guided by the psychological dimensions of professional activity.
Keywords: Diabètes; Education Thérapeutique du Patient; Explication; Clinique de l'Activité